INTRODUCING TETRACYS MOTIFS AT TWO DIFFERENT SITES RESULTS IN A FUNCTIONAL DOPAMINE TRANSPORTER - (:unkn) unknown (AKADEMIAI KIADO ZRT, 2009)
We have introduced tetracysteine motifs into different positions of the dopamine transporter (DAT) for specific FlAsH labeling. Two of the constructs expressed at the cell surface and were functional as determined by [H-3] dopamine uptake experiments. The N-terminally modified transporter showed uptake levels comparable to the wild-type DAT, while the construct with tetracysteine motif at position 511 displayed an uptake level about 1/3 of its wild-type counterpart. In addition, these two transporter constructs were visualized on the cell surface following labeling with a fluorescent cocaine analog. YFP introduced into the same N-terminal position was also shown to have surface staining in agreement with activity tests. We propose that these two sites are suitable targets for tetracysteine labeling to be used in FlAsH staining studies, while p134, p342, p427, p433 and p517 sites are not.
Keywords: Dopamine transporter; FlAsH; tetracysteine; fluorescent labeling; confocal; G-PROTEIN; COCAINE; CONFORMATION; GLUTAMATE; SURFACE